Analysis of Development Potential of Sheep in Deli Serdang Regency, North Sumatra Province - E. Mirwandhono; Hasnudi; Ardiansyah, Rizky (Jurnal Peternakan Integratif, 2021)
Deli Serdang Regency is one of the largest sheep-producing areas in North Sumatra Province. Analysis of the potential for sheep development in the area needs to be done, to achieve various goals. This study aims to identify livestock resources, base or non-base areas and sheep capacity as well as to find the right strategy for the development of a sheep business in Deli Serdang Regency. The method used in this research is the stratified sampling method in all districts in Deli Serdang Regency and purposive sampling method in three districts, namely, Percut Sei Tuan, Hamparan Perak, and Galang as a method of determining the area. Interviews with 10 breeders from each sub-district were conducted to gather information related to sheep farming in the area. Data analysis was performed with descriptive analysis, location quation (LQ), animal density, analysis of feed concentration index , and capacity analysis for Livestock Population Increase (LPIC). The results showed that the livestock resources in Deli Serdang Regency have the potential to develop sheep farming businesses. There are 13 districts which are base areas with a capacity of livestock unit.